Marketing Innovations of Countries in the Context of the Implementation of the Sustainable Development Goals - Taraniuk Leonid; Taraniuk Karina; Korsakiene Renata; Miceikienė Astrida (Management Systems in Production Engineering)
The primary goal of the study is to evaluate the marketing of innovations by business entities in various countries in the context of the implementation of the Sustainable Development Goals (SDGs). This scientific research includes a bibliometric analysis of academic works on the marketing of innovations by companies within the sustainable business system. An analysis of the competitiveness of the components of innovation marketing in countries with developed and developing economic systems was conducted to identify leading, lagging, and intermediate zones where the studied countries are located. Ranges of an integral indicator of the level of competitiveness of innovation marketing components in countries, in the context of achieving the SDGs, were established. The scientific hypothesis posits the potential for using parametric research methods and the synthesis of innovation marketing indicators aligned with the SDGs to determine the level of competitiveness of innovation marketing in countries with different levels of economic development. The research design involves the use of synthesis methods, parametric, graph-analytical, and criterion methods, and procedures for analyzing innovation marketing in countries. The number of subjects includes five studied countries. The main results include a literature review of academic research on innovation marketing. The study also provides an analysis of the competitiveness of innovation marketing in the studied European and Eastern European partnership countries, determining their level of competitiveness. The findings highlight the importance of innovation marketing in achieving the SDGs and can be useful for further scientific research in this area and for practical application.